Crime, Violence, and Community-Based Prevention in Honduras - Berg, Louis-Alexandre (World Bank, Washington, DC, 2015)
Violent crime has emerged as a growing development challenge, affecting large segments of societies, and taking a severe toll on economic development. In many high crime environments, weak institutions, fiscal constraints, and political resistance have undermined the effectiveness of development programs and threatened their sustainability. The World Bank has begun to confront this challenge. The country of Honduras is the most violent in the world as measured by its homicide rate, which reached 90.4 per 100,000 inhabitants in 2012. This report presents the findings of a study of crime dynamics and prevention practices focused around a comparison of nine neighborhoods in three of the most violent cities in Honduras: La Ceiba, El Progreso, and Choloma. The research revealed that although the transnational drug trade, economic downturn, and political crisis have deepened the country’s vulnerability, some neighborhoods have successfully prevented crime. Drawing from extensive qualitative research in these neighborhoods, the study identified practices that communities pursue to prevent violence through collective responses. It also examined the characteristics of communities, societal factors, and institutional context that have enabled or constrained these responses. The research points to measures that can be built upon, scaled up, and tested through future research and programming to strengthen community-based crime prevention. It illustrates how deep examination of the dynamics of insecurity - and the ways communities manage it - can inform efforts to improve public safety in violence-prone countries.